Reassessment of the spinose polytoechiid brachiopod pinatotoechia Benedetto from the Lower Ordovician of western Argentina - Benedetto, Juan Luis Arnaldo (2016)
PINATOECHIA (type species Pinatotoechia acantha Benedetto) is a peculiar spinose polytoechiid hitherto confined to the Famatina-Puna volcanic-arc system fringing the Andean margin of Gondwana during the Ordovician. This genus was described originally from the volcanosedimentary Aguada de la Perdiz Formation exposed west of Salar del Rincón in the Puna region of NW Argentina, a few kilometers from the international border with Chile. According to the associated trilobites as well as the graptolites from correlatable units, the age of these beds is latest Floian-early Dapingian. New and better preserved specimens of Pinatotoechia acantha were subsequently collected from the nearly coeval volcaniclastic Suri Formation of the Famatina Range (Benedetto, 2003). Rubel (2007), in the supplement of the revised Treatise, put in synonymy Pinatotoechia Benedetto with Tritoechia Ulrich and Cooper arguing that the spines of the former are, in fact, identical to the aditicules of the type species Tritoechia typica (Schuchert and Cooper, 1932). The purpose of this paper is to present conclusive evidence on the presence of true hollow spines erected on the tops of costellae in order to support the validity of the genus and to improve its description and illustration. Likewise, the ventral interior of Pinatotoechia is redescribed and reillustrated to show that its pseudospondylium and ventral muscle pattern clearly differ from those of Tritoechia.